Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 7 - Section 7.3 - Simplifying Radicals, the Distance Formula, and Circles - 7.3 Exercises: 57

Answer

$-2\sqrt[3] 2$

Work Step by Step

$\sqrt[3] -16=\sqrt[3] (-8\times2)=\sqrt[3] -8\times\sqrt[3] 2=-2\sqrt[3] 2$ We know that $\sqrt[3] -8=-2$, because $(-2)^{3}=-8$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.